(untitled) (Bangladesh Journal of Botany, 2022)
Effects of vehicular emission on two plants Amaranthus spinosus Linn. and Croton bonplandianum Baill, collected from polluted site and from relatively less polluted site/control site of Kolkata city of West Bengal, India was studied. Photosynthetic pigment content, proline content, phosphatase activity and Hill activity, heavy metal contents and their relevance to be used as phytoremediators was investigated. Decrease in pigment content and increase in proline content and phosphatase activity was observed in the plants from polluted areas. Micromorphological studies revealed the effect of automobile emission on epidermal cells and stomatal size on both the experimental plants. Data indicated that between the two plants, A. spinosus was more susceptible and C. bonplandianum was more tolerant to vehicular pollution. Bangladesh J. Bot. 51(2): 207-216, 2022 (June)